Business Development of Dental Services Marketing in Hospital: A Systematic Review - Ekasari, Ferti Dwi; Sulistiadi, Wahyu (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2020)
One of the health services in the hospital is dental and oral health care. Hospitals must establish a good marketing strategy for their organizations in an effort to continue to improve or maintain the expected position. Based on the above, it is necessary to know what efforts can be made by dental outpatient clinics in developing marketing of dental and oral health services in dental clinics in hospitals to increase patient visits to hospital dental clinics. This study use Systematic Review with PRISMA method retrieved from online database such as ProQuest, willy online, J Store, Scopus and Google Schoolars using a keyword “Dental services", "Dental marketing", "Marketing mix" and "Hospitals". The end of this search got 8 journals. Based on the results of research in several journals it was found that there were many ways to market dental polyclinics in hospitals. starting from strategic planning in setting up a dental polyclinic in a hospital it must be well planned. So that the investment or business that will be run can be successful, then beforehand it is necessary to do the right competitive strategy. An increase in patient visits at the hospital dental clinic can be done with one of the 3.0 marketing approaches. The components like physical evidence, people, and process were mixed to the form of the Service Marketing Mix. Marketing media can be done directly or by utilizing information media that can be accessed by many people online. Marketing efforts must also be in accordance with the law and medical ethics. Business development of dental services must be carried out and in accordance with a good marketing strategy. Good dental marketing will increase patient visits at the hospital.